Kongresy i zjazdy pedagogiczne w rozwoju polskiej myśli i praktyki edukacyjnej (do 1939 roku) - Jamrożek, Wiesław (Wydawnictwo Naukowe UAM, 2015)
This text first presents two congresses that were organized in Lviv, still in the period of national subjugation: the First Polish Pedagogical Congress [PL: Kongres Pedagogiczny], which took place on July 17-19, 1894, and the Second Polish Pedagogical Congress, which was held on November 1-2, 1909. Next, the text describes congresses (meetings) that were organized after Poland had regained independence: the National Educational Meeting [PL: Ogólnopolski Zjazd Oświatowy] in Warsaw, which took place on April 14-17, 1919 (and which went down in history as “Teachers’ Sejm” [PL: Sejm Nauczycielski]), the First Pedagogical Congress, which was organized on July 8-10, 1929 (i.e. during the Polish General Exhibition [PL: Powszechna Wystawa Krajowa]), the Second Pedagogical Congress, held in Vilnius on July 4-8, 1931, the Third Pedagogical Congress, organized in Lviv on June 17-21, 1933, and the Fourth Pedagogical Congress, which took place in Warsaw on May 27-29, 1939 (in the face of the growing threat from Nazi Germany). This book also analyzes the course and outcome of the National Child Congress [PL: Ogólnopolski Kongres Dziecka], which took place in Warsaw on October 1-4, 1938. The abovementioned meetings and congresses played an important role in developing educational thought and practice in the Polish lands at the turn of the 20th century and in Poland during the interwar period. A wide range of topics were discussed, from problems associated with school and out-of-school education, and issues related to both a child’s and an adult’s education to topics dealing with so-called educational ideology and child care (at different stages of a child’s development and by taking into account children with disabilities).

Ramy chronologiczne publikacji obejmują przełom XIX i XX stulecia oraz okres Polski międzywojennej. Organizowane w tym czasie kongresy i zjazdy pedagogiczne zwoływane przez środowiska nauczycielskie i oświatowe oraz związanych z nimi teoretyków edukacji odegrały doniosłą rolę w rozwoju ówczesnej polskiej myśli i praktyki edukacyjnej. W książce zaprezentowano dwa kongresy lwowskie zorganizowane przed odzyskaniem niepodległości: Pierwszy Polski Kongres Pedagogiczny (17–19 lipca 1894 roku, podczas Powszechnej Wystawy Krajowej we Lwowie) oraz Drugi Polski Kongres Pedagogiczny (1–2 listopada 1909 roku), a następnie kongresy (zjazdy) urządzane już po odzyskaniu niepodległości: Ogólnopolski Zjazd Oświatowy (14–17 kwietnia 1919 roku w Warszawie, który przeszedł do historii pod nazwą Sejmu Nauczycielskiego), Pierwszy Kongres Pedagogiczny (8–10 lipca 1929 roku, podczas Powszechnej Wystawy Krajowej w Poznaniu), Drugi Kongres Pedagogiczny (4–8 lipca 1931 roku w Wilnie), Trzeci Kongres Pedagogiczny (17–21 czerwca 1933 roku we Lwowie), Czwarty Kongres Pedagogiczny (27–29 maja 1939 roku w Warszawie, w obliczu narastającego zagrożenia ze strony Niemiec hitlerowskich). Przedmiotem rozważań są także przebieg i rezultaty obrad Ogólnopolskiego Kongresu Dziecka (1–4 października 1938 roku w Warszawie). Tematyka podejmowana na wymienionych zjazdach i kongresach pedagogicznych była rozległa i obejmowała zagadnienia dotyczące zarówno edukacji szkolnej, jak i oświaty pozaszkolnej, problematykę edukacji dzieci oraz kształcenia dorosłych, tematy z zakresu tzw. ideologii i teleologii wychowawczej, opieki nad dzieckiem (w różnych fazach jego rozwoju i z uwzględnieniem dzieci niepełnosprawnych), a także szeroko rozumianej teorii pedagogicznej i nowatorstwa pedagogicznego.
Pedagogical Congresses and Meetings and the Development of Polish Educational Thought and Practice (until 1939)
Keywords: edukacja; myśl pedagogiczna; praktyka edukacyjna; kongresy i zjazdy pedagogiczne